2013
DOI: 10.1016/j.febslet.2013.07.016
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of an isopenicillin N synthase complex with an ethereal substrate analogue reveals water in the oxygen binding site

Abstract: Edited by Peter Brzezinskiis converted to a bioactive penam product. ACmT and ACmaT differ from each other only in the stereochemistry at the b-carbon atom of their third residue. These substrates both contain a methyl ether in place of the isopropyl group of ACV. We report an X-ray crystal structure for the anaerobic IPNS:Fe(II):ACmT complex. This structure reveals an additional water molecule bound to the active site metal, held by hydrogen-bonding to the ether oxygen atom of the substrate analogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
(83 reference statements)
0
11
0
Order By: Relevance
“… 28 The overall fold of IPNS is based on a distorted double-stranded β-helix (DSBH or ‘jelly roll’) core; this scaffold supports the triad of Fe( ii ) binding residues, and was subsequently shown to be conserved in 2OG oxygenases, including DAOCS. 53 , 59 As shown in subsequent anaerobic structures obtained in the presence of ACV and Fe( ii ), Gln330 ( ref. 28 and 60 ) (and one iron coordinating water) is displaced from the active site on binding of ACV, triggering conformational rearrangement of the C -terminal region (Asn326-Thr331).…”
Section: Isopenicillin N Synthasementioning
confidence: 70%
“… 28 The overall fold of IPNS is based on a distorted double-stranded β-helix (DSBH or ‘jelly roll’) core; this scaffold supports the triad of Fe( ii ) binding residues, and was subsequently shown to be conserved in 2OG oxygenases, including DAOCS. 53 , 59 As shown in subsequent anaerobic structures obtained in the presence of ACV and Fe( ii ), Gln330 ( ref. 28 and 60 ) (and one iron coordinating water) is displaced from the active site on binding of ACV, triggering conformational rearrangement of the C -terminal region (Asn326-Thr331).…”
Section: Isopenicillin N Synthasementioning
confidence: 70%
“…[29,44] Similarly, analogues in which d-valine is replaced by d-serine, d-glutamic acid, dasparagine, d-O-methylthreonine or d-methionine are not are not turned over by IPNS. [44,[51][52][53] Crystallographic studies of the IPNSÀ FeÀ ACtaI complex revealed a similar structure to that of native IPNSÀ FeÀ ACV (Figure 20A). However a significant difference was observed in the coordination at the iron centre: the methylsulfide group of thia-allo-isoleucine was ligated to iron trans to Asp216, where it presumably prevents dioxygen binding, [29] in a similar manner to substrate analogue AhCmC.…”
Section: Figure 19mentioning
confidence: 79%
“…It has been postulated that similar stabilising forces would not be present in the IPNSÀ FeÀ ACmaT complex, in which the stereochemistry about the threonine β-carbon would orient this away from the additional water ligand. [52] Thus oxygen binding and subsequent substrate turnover would be possible with ACmaT, but not for ACmT. Taken together, these studies with polar amino acids in place of ACV valine suggest that the replacement of valine with such residues can prevent the binding of dioxygen -due either to direct, ligating interactions of the amino acid side chain at the co-substrate binding site, or to tight binding via a water ligand -preventing oxidative turnover.…”
Section: Crystallisation Of Ipns With Substrate Analogues Bearing Polar Side Chains In Place Of Valinementioning
confidence: 93%
See 2 more Smart Citations